A Sámi Community Wins Case against the Swedish State in the Supreme Court - Øyvind Ravna (Arctic Review on Law and Politics, 2020)
On 23 January 2020, the Supreme Court of Sweden delivered an historic verdict in favour of the Girjas sameby in a lawsuit against the Swedish State over a long-standing dispute over the right to administer hunting and fishing rights in the Girjas land management area. Rooted in Sámi customary law, ILO Convention 169 and the UN Declaration of Indigenous Peoples, the verdict is a milestone in the development of Sámi law in Sweden. It may also have an impact on the other Nordic countries, in particular Norway.